Interesterified fat maternal consumption before conception programms memory and learning of adulthood offspring: How big is this deleterious repercussion?. (15th May 2022) - D'avila, Lívia Ferraz; Dias, Verônica Tironi; Trevizol, Fabíola; Metz, Vinícia Garzella; Roversi, Karine; Milanesi, Laura; Maurer, Luana Haselein; Baranzelli, Júlia; Emanuelli, Tatiana; Burger, Marilise Escobar
Abstract: In recent years, interesterified fat (IF) has largely replaced trans fat in industrialized food. Studies of our research group showed that IF consumption may not be safe for central nervous system (CNS) functions. Our current aim was to evaluate IF maternal consumption before conception on cognitive performance of adult rat offspring. Female Wistar rats were fed with standard chow plus 20% soybean and fish oil mix (control group) or plus 20% IF from weaning until adulthood (before mating), when the diets were replaced by standard chow only. Following the gestation and pups' development, locomotion and memory performance followed by neurotrophin immunocontent and fatty acids (FA) profile in the hippocampus of the adulthood male offspring were quantified. Maternal IF consumption before conception decreased hippocampal palmitoleic acid incorporation, proBDNF and BDNF levels, decreasing both exploratory activity and memory performance in adult offspring. Considering that, the adult male offspring did not consume IF directly, further studies are needed to understand the molecular mechanisms and if the IF maternal preconception consumption could induce the epigenetic changes observed here. Our outcomes reinforce an immediate necessity to monitor and / or question the replacement of trans fat by IF with further studies involving CNS functions. Graphical Abstract: ga1 Highlights: IF maternal consumption before conception alter the brain fatty acids composition. IF before conception impairs memory performance in adulthood. IF before conception decreases exploratory activity in adult male offspring. Maternal IF before conception decreases BDNF levels in hippocampus in adulthood. Maternal IF before conception reduces hippocampal proBDNF immunoreactivity.